(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Task-based language teaching methodology is one of the effective approaches in developing students’ language skills. In this method, the learning process is focused on solving real-life tasks and problems, giving students the opportunity to use the language in a practical way. The abstract examines the main principles, advantages and role of task-based learning in students’ language learning. In this article, the theoretical basis of task-based language teaching, its importance in increasing student motivation and developing interaction, and the role of the teacher in providing guidance are analyzed in detail. Tasks aimed at developing students’ self-assessment and problem-solving skills are important in strengthening their language skills.